Event-Related Potentials and Evoked Potentials - Sittiprapaporn, Phakkharawat (IntechOpen, 2017)
This edited volume Event-Related Potentials and Evoked Potentials is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of medicine and health sciences. The book comprises single chapters authored by various researchers and edited by an expert active in the field of event-related potential (ERP). An event-related potential (ERP) is the measured brain response that is the direct result of a specific sensory, cognitive, or motor event. Each chapter is complete in itself but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors in noninvasive means of evaluating brain functioning and opens new possible research paths for further novel developments.